Er/Yb Double-Clad Fiber Laser with fs-Laser Inscribed Plane-by-Plane Chirped FBG Laser Mirrors - Theodosiou, Antreas; Aubrecht, Jan; Peterka, Pavel; Kašík, Ivan; Todorov, Filip; Moravec, Ondřej; Honzátko, Pavel; Kalli, Kyriacos (My University, 2019)
We present an efficient monolithic fiber laser incorporating fiber Bragg grating (FBG) mirrors inscribed directly into the active fiber using a femtosecond laser. The FBGs are inscribed in an erbium/ytterbium co-doped fiber using the direct-write, plane-by-plane femtosecond laser inscription method, which allows for complete spatial control of the refractive index change in the fiber core. This approach offers a significant advantage, as we eliminate the fiber splices typically required between the active and passive fibers that would, otherwise, incorporate the FBG. The gratings were characterized in transmission and reflection, and the performance of the fiber laser was recorded when the fiber was coiled into a circular and kidney shape. The kidney shape of the fiber coil improved the laser slope efficiency, as the inner cladding of the active fiber had a circular shape. Our results show that the control of the grating inscription parameters using the plane-by-plane inscription method can result in an efficient monolithic fiber laser.
Keywords: Bragg gratings; Chirped gratings; Femtosecond lasers; Fiber lasers